O profmat e a formação continuada do professor de matemática da educação básica - Veloso, Rebeca Nunes (Universidade Federal Rural do Semi-Árido, 2017)
This research intends to analyze the Professional Master of Mathematics in a National Network (PROFMAT). Our goal is to analyze the continuing education of elementary school math teachers, and also to examine the post-graduation degree according to some of these educationalists' points of view, such as: Tardif (2002), Gatti (2010) and Vicente & Resende (2016). For this reason, we present some of the official educational documents of PROFMAT, we also analyze some of the dissertations and we introduce a questionnaire replied by 14 formed students from this Master Program. This questionnaire presents the same reports of these living experiences in the Master Program, their expectation and negative and positive critics about the program. In that end, we want to contribute to the discuss concerning to teacher's formation of Brazil and to bring some critics about this recent project of education in our country
Keywords: Educação continuada; Formação de professores; PROFMAT; Continuing education; Teachers formation; PROFMAT; CIENCIAS EXATAS E DA TERRA::MATEMATICA